Canadian Cardiovascular Society Consensus Conference guidelines on heart failure – 2008 update: Best practices for the transition of care of heart failure patients, and the recognition, investigation and treatment of cardiomyopathies - Arnold, J Malcolm O (Pulsus Group Inc, 2008)
Heart failure is a clinical syndrome that normally requires health care to be provided by both specialists and nonspecialists. This is advantageous because patients benefit from complementary skill sets and experience, but can present challenges in the development of a common, shared treatment plan. The Canadian Cardiovascular Society published a comprehensive set of recommendations on the diagnosis and management of heart failure in January 2006, and on the prevention, management during intercurrent illness or acute decompensation, and use of biomarkers in January 2007. The present update builds on those core recommendations. Based on feedback obtained through a national program of heart failure workshops during 2006 and 2007, several topics were identified as priorities because of the challenges they pose to health care professionals. New evidence-based recommendations were developed using the structured approach for the review and assessment of evidence that was adopted and previously described by the Society. Specific recommendations and practical tips were written for best practices during the transition of care of heart failure patients, and the recognition, investigation and treatment of some specific cardiomyopathies. Specific clinical questions that are addressed include: What information should a referring physician provide for a specialist consultation? What instructions should a consultant provide to the referring physician? What processes should be in place to ensure that the expectations and needs of each physician are met? When a cardiomyopathy is suspected, how can it be recognized, how should it be investigated and diagnosed, how should it be treated, when should the patient be referred, and what special tests are available to assist in the diagnosis and treatment? The goals of the present update are to translate best evidence into practice, apply clinical wisdom where evidence for specific strategies is weaker, and aid physicians and other health care providers to optimally treat heart failure patients, resulting in a measurable impact on patient health and clinical outcomes in Canada.